Pogge on Poverty: Contribution or Exploitation?. (9th August 2013) - Øverland, Gerhard
Abstract: Thomas Pogge argues that affluent people in the developing world have contribution‐based duties to help protect the poor. And it follows from Pogge's most general thesis that affluent people are contributing to most, if not all, instances of global poverty. In this article I explore two problems with Pogge's general thesis. First, I investigate a typical way in which affluent people would be contributing to global poverty according to Pogge: that affluent countries use their superior bargaining power to get poor countries to accept trading schemes that are unduly favourable to the affluent. I suggest that this type of relation is best understood as exploitation, and that Pogge's general thesis is better understood as a thesis about how affluent people exploit poor people rather than about how they contribute to poverty. Second, I argue that the exploitation does not have the normative content of doing harm. Although exploiting people is often morally wrong, it is not at all clear how demanding exploitation‐based duties are.